Cornelia de Lange syndrome- Report of the Second Case from Ahvaz - Ali Ahmadzadeh; Azin Ahmadzadeh; Mohammadreza Fathi; Arash Ahmadzadeh (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Cornelia de Lange syndrome (CdLS) is a rare hereditary disease, characterized by severe growth retardation, microcephaly, and limb anomalies, distinctive dysmorphic features and mental retardation. The etiology is not still clear. However, it is caused by mutation of the nipped- B- like (NIPBL) gene in approximately 50% of cases. Here, we report our second case of CdLS from Ahvaz after 19 years. The patient was a 15- month girl admitted in our center due to urinary tract infection. She had characteristic dysmorphic features, microcephaly, growth and developmental retardation, upper and lower limb defects, associated with renal cyst and dysplasia. CdLS is a rare hereditary syndrome with severe congenital anomalies. The diagisis is practically based on the characteristic phenotype. The further prognosis is poor.